2019
DOI: 10.1371/journal.pone.0224427
|View full text |Cite
|
Sign up to set email alerts
|

Integrating interconception care in preventive child health care services: The Healthy Pregnancy 4 All program

Abstract: BackgroundMost parents with young children pay routine visits to Well-Baby Clinics, or so-called Preventive Child Health Care (PCHC) services. This offers a unique opportunity to promote and deliver interconception care. This study aimed to integrate such care and perform an implementation evaluation.MethodsIn seven Dutch municipalities, PCHC professionals were instructed to discuss the possibility of an interconception care consultation during each routine six-months well-baby visit. The primary outcome of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
0
14
0
2
Order By: Relevance
“…Six studies were identified, scoring high (1) to moderate (5) quality. Pilot studies focused on outcomes, including nutritional supplementation, mental health outcomes, interconception care provision, and contraception and process evaluation of the studies 25–31 . Interconception care interventions can include risk assessments leading to tailored care, complex interventions and educational components, including counselling, multivitamin supplementation, peer support groups, walking programmes, contraception, mental health and substance support, and dental care 25,26 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies were identified, scoring high (1) to moderate (5) quality. Pilot studies focused on outcomes, including nutritional supplementation, mental health outcomes, interconception care provision, and contraception and process evaluation of the studies 25–31 . Interconception care interventions can include risk assessments leading to tailored care, complex interventions and educational components, including counselling, multivitamin supplementation, peer support groups, walking programmes, contraception, mental health and substance support, and dental care 25,26 .…”
Section: Resultsmentioning
confidence: 99%
“…Pilot studies focused on outcomes, including nutritional supplementation, mental health outcomes, interconception care provision, and contraception and process evaluation of the studies. [25][26][27][28][29][30][31] Interconception care interventions can include risk assessments leading to tailored care, complex interventions and educational components, including counselling, multivitamin supplementation, peer support groups, walking programmes, contraception, mental health and substance support, and dental care. 25,26 Although none of these interventions were followed up to assess infant outcomes, they have improved women's uptake of multivitamins supplements, mental health support, use of contraception, physical exercise and dental care.…”
Section: Findings From Pilot Studies On Interconception Care During T...mentioning
confidence: 99%
See 1 more Smart Citation
“…83 84 Mothers regularly attend their child's health care visits even if they do not seek care for themselves between pregnancies. 85 Given children typically attend 8 to 10 WCVs in the first 2 years of life, the WCV offers a consistent and repeated point of maternal contact and chance for intervention. 86 Finally, prior studies demonstrate that most mothers accept inquiry about their own health behaviors and referral for services at visits with their pediatric care providers.…”
Section: Improving Equitable Access To Care Through Icc Programsmentioning
confidence: 99%
“…Initiatives aimed at increasing the awareness of pregnancy preparation and the availability of pregnancy-related care have been launched ( van der Zee et al , 2011 ; Lagendijk et al , 2019a ; Sijpkens et al , 2019 ). A striking example is the so-called ‘Healthy Pregnancy 4 All-2’ program which aims to identify vulnerable mothers living in underprivileged areas and young children at risk of adverse health outcomes to offer them pregnancy-related care ( Lagendijk et al , 2019a ).…”
Section: Poor Pregnancy Outcomes and The Underpinning Mechanismsmentioning
confidence: 99%